Üniversite Yaşamında Yakın İlişkiler ve İstismar - ÖNGÜN, ESEN; ÜNSAL, GÜL (My University, 2018)
Romantik ilişki istismarı, geçmişteki veya şimdiki sevgiliüzerinde güç kullanılan ve kontrol kurulan, tacize maruzbırakan ve zorlayıcı davranışları içeren bir durumdur.Romantik ilişkilerde yaşanan istismar, partner/eş istismarıolarak da anılmaktadır. İstismar ve şiddet kavramları özellikle fiziksel istismar ile fiziksel şiddet söz konusu olduğunda net olarak birbirinden ayrılamamakta, her ikisi de benzer anlamda kullanılmaktadır. Şiddet, ilişkide genelliklebiri tarafından diğerini kontrol altında tutmak için kullanılır. Romantik ilişkide şiddet duygusal, fiziksel ve cinselsaldırganlığı içermektedir. Üniversite yıllarına denk düşengeç ergenlik döneminde de romantik ilişkilerde istismarasık rastlanmaktadır. Bu derlemede üniversite öğrencileriarasında istismar yaşantısının, yakın ilişkilerdeki risklerive sonuçları, bu ilişkilerdeki şiddetin çeşitleri ve etkileri elealınarak, önleyici yolları tartışılmıştır.

Abusive romantic relationship is a condition which consists of exerting power, control and harassment and coercive behaviours on the present or previous lover. Abusive behaviours experienced in romantic relationships are also called as partner/spouse abuse. The concepts of abuse and violence especially physical abuse and physical violence can not be differentiated from each other so both of them are used to express similar concepts. Violence in a relationship is generally used to keep the partner in control. Violence in romantic relationship includes emotional, physical and sexual aggression. During late adolescent period which corresponds also to university years abuse in romantic relationships is frequently encountered. In this review, abusive behaviours, among university students their risks and consequences in intimate relationships, types of violence used in these relationships and their effects were investigated and preventive measurements were discussed.
Intimate Relationships and Abuse in University
Keywords: Sağlık Bilimleri ve Hizmetleri; Sağlık Politikaları ve Hizmetleri; Hemşirelik